Feasibility of Catfish Chips Business in Kampung Lele Boyolali - Rahmadhani, Octaria Nur; Lestari, Retna Dewi; Sepfrian, Bimoseno (LPPM Universitas Duta Bangsa Surakarta, 2025)
The diversification of the Kampung Lele business through catfish chips products aims to increase the income of farmers and absorb the relatively large fresh catfish sizes, namely 1 kg containing 3, 4, 5 that are not sold. In reality, catfish chips products face obstacles in marketing because there is no team that connects the sale of catfish chips products outside Java and people do not buy catfish chips every day, so it has not been able to increase the income of catfish farmers in Kampung Lele Boyolali. The purpose of this study is to determine the market potential of catfish chips in Kampung Lele Boyolali. The analytical methods used were Return on Investment (ROI) and marketing margin analysis. The ROI analysis showed an efficiency of 79%, and a marketing margin of Rp 12,000 per three catfish chip variants. Therefore, catfish chip production in Kampung Lele Boyolali has the potential to be further developed with a market development strategy that accommodates and is appropriate for the future.